Pakarena Dance as a Medium for Character Education: A Phenomenological Study in South Sulawesi Elementary Schools - Sudarmin; Abdul Malik; Nasir (Journal of Local Wisdom in Education, 2025)
This study investigates the role of Pakarena dance extracurricular activities in strengthening character values among elementary school students in Maros Regency, South Sulawesi, Indonesia. As a traditional dance rich in cultural symbolism, Pakarena offers a unique and contextually grounded medium for character education, aligning with the growing need to incorporate local wisdom into holistic educational practices. Addressing the gap in existing literature, which often emphasizes technical dance instruction over educational impact, this study adopts a qualitative phenomenological approach to explore students’ lived experiences and the values internalized through dance participation. Data were collected through semi-structured interviews with students, teachers, and parents, as well as participatory observation of dance rehearsals and performances, and document analysis. The findings reveal that consistent engagement in Pakarena dance fosters key character values, including discipline, hard work, cooperation, responsibility, creativity, curiosity, and self-confidence. These outcomes are attributed to both the structured guidance of instructors and the intrinsic moral messages embedded in the dance’s movements and rituals. The novelty of this research lies in its integration of South Sulawesi’s cultural heritage into a pedagogical framework for character development, thereby bridging local traditions with national educational goals. This study contributes to the advancement of character education by providing an innovative, culturally responsive model that supports moral, emotional, and social growth in elementary students while promoting the preservation and appreciation of indigenous knowledge systems.